Preserved Low-Frequency Hearing Following 20-mm Cochlear Implantation. Issue 2 (February 2015) - Brown, Kevin D.; Melton, Myles F.; Shonfield, Hannah; Kraskin, Michelle; Wolf, Jennifer
Abstract : Objective: To determine the preservation of pure tone thresholds for a series of cochlear implant patients who underwent atraumatic round window insertion with a new thin 22-mm electrode to a 20-mm depth. Study Design: Retrospective, within-subject repeated measures design. Setting: Tertiary care hospital. Patients: Nine sequential cochlear implant patients with functional preoperative acoustic hearing (defined as low-frequency pure tone average thresholds ⩽90 dB). Intervention: Therapeutic. Main Outcome Measure: Pure tone thresholds after cochlear implantation. Results: Low-frequency hearing preservation was achieved in all cases. Less than 10 dB average change was seen for low-frequency pure tone average measures (125, 250, 500, and 1, 000 Hz) at 6 and 12 months following cochlear implantation. Conclusions: Atraumatic round window insertion with a thin 22-mm electrode to a 20-mm depth results in dramatically high levels of acoustic hearing preservation among CI patients.